Surgical Outcomes after Abdominoperineal Resection with Sacrectomy and Soft Tissue Reconstruction: Lessons Learned - Manrique, Oscar J.; Rajesh, Aashish; Asaad, Malke; Bakri, Karim; Tran, Nho V.; Houdek, Matthew T.; Dozois, Eric J.; Rose, Peter S. (Journal of Reconstructive Microsurgery, 2020)
Background Abdominoperineal resection (APR), which involves resection of the rectum, anal canal, and perianal skin, results in a large dead space in the pelvis, devascularized tissues, and high bacterial loads. This predisposes to wound complications, especially in the setting of neoadjuvant chemoradiotherapy. Additional sacral resection further compounds these effects. We aimed to assess perineal wound outcomes and complications in patients who underwent flap reconstruction for APR with sacrectomy (APRS) at our institution.Methods We reviewed the charts of all patients who underwent flap reconstruction for APRS over a 20-year period (1999–2018). Medical comorbidities, details of the surgical procedure, and major and minor wound complications were recorded and analyzed.Results Forty-six patients underwent flap reconstruction following APRS—28 (60%) for colorectal cancer, 8 (17%) for sacral chordoma, and 10 diagnosed with other malignant histologies. Rectus abdominis myocutaneous (RAM) flap reconstruction was used in 42 patients (91%). The median time to the first major perineal complication was 111 days (interquartile range: 22–660 days). Half of our cohort (n = 23) experienced a major perineal complication. No significant differences were found in major or minor perineal or abdominal wall complications between RAM flap and other flaps. APR with high sacrectomy was performed in 27 patients (59%) and was associated with significantly increased full-thickness dehiscence in the perineal region when compared with APR with low sacrectomy, 33 versus 0%, respectively (p = 0.0076). Complete flap loss occurred in one patient.Conclusion The RAM flap was the workhorse flap for pelvic reconstruction following APRS in our cohort. Wound complications are common following APRS. High sacrectomy is associated with higher incidence of complications compared with low sacrectomy. Optimal surgical planning and patient counseling is fundamental to improve current surgical outcomes.
Keywords: abdominoperineal resection; sacrectomy; flap